A NEW INTEGRATED INFORMATION SEEKING MODEL BASED ON INCONGRUITY AND FOUR HUMOURS (Journal of Economic Research & Business Administration, 2019)
There are various conceptual models or frameworks from different disciplines and domains. These models have ben built to give explanation to the related issues on information seeking and processing especially for the information and the knowledge oriented disciplines and domains. The models in literature dealt with different user groups and information seeking behaviors of these user groups. In this paper, with focusing on, an integrative conceptual model for information processing and seeking will be developed from the perspective of information systems modeling. Accordingly, this paper will first provide background information and suggest a new model based on these information sources. Then, the suggested model will be interlinked with the humoral theory in order to amplify its explanatory and integrative power. To build a suggestion model, this paper will also provide directions for possible new work. The suggested model is creating interlinked connection with the concept of incongruity and the humoral theory.